The production of lactic acid from chemi-thermomechanical pulps using a chemo-catalytic approach - Wu, Jie; Kim, Kwang Ho; Jeong, Keunhong; Kim, Dongwoo; Kim, Chang Soo; Ha, Jeong-Myeong; Chandra, Richard P.; Saddler, Jack N. (Elsevier BV, 2021)
Previous work has shown that sulfonation and oxidation of chemi-thermomechanical pulps (CTMPs) significantly enhanced enzyme accessibility to cellulose while recovering the majority of carbohydrates in the water-insoluble component. In the work reported here, modified (sulfonated and oxidized) CTMPs derived from hard-and softwoods were used to produce a DL-mix of lactic acid via a chemo-catalytic approach using lanthanide triflate (Ln (OTf)(3)) catalysts (Ln = La, Nd, Er, and Yb). It was apparent that sulfonation and oxidation of chemithermomechanical pulps (CTMPs) also enhanced Ln(OTf)(3) catalyst accessibility to the carbohydrate components of the pulps, with the Er(OTf)(3) catalysts resulting in significant lactic acid production. Under optimum conditions (250 degrees C, 60 min, 0.5 mmol catalyst g-1 biomass), 72% and 67% of the respective total carbohydrate present in the hard-and-softwood CTMPs could be converted to lactic acid compared to the respective 59% and 51% yields obtained after energy-intensive ball milling.